Solid waste synthesis activator and preparation and application thereof
By using solid waste synthesis excitants to treat lithium slag and using solid waste materials such as calcium carbide slag to build a stable three-dimensional framework network, the problem of uncured lithium slag heavy metals is solved, and harmless and resource-based utilization is achieved. The process is simple and cost-effective.
Patent Information
- Application Number
- CN202411793676.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to effectively and harmlessly utilize lithium slag in a resource-based manner, especially since the heavy metal has not been cured and has been transferred, resulting in heavy metal leaching problems in the treatment product.
A solid waste synthesis excitant is used, which consists of calcium carbide slag, desulfurized gypsum, silica fume, glass powder, thermally activated red mud, silicate and regulator (such as nano-alumina, aluminum sulfate, sodium metaaluminate). By adjusting the silicon-alumina ratio and introducing regulators, a stable three-dimensional framework network is constructed to improve the curing effect of heavy metals.
The harmless treatment of lithium slag is achieved, the resulting geological polymer is harmless and can be directly recycled and recycled. The process is simple, the cost is low and there is no pollution by-product.
Smart Images

Figure BDA0005176097020000081 
Figure BDA0005176097020000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of harmless treatment of industrial solid waste, and in particular to a solid waste synthesis stimulator and the preparation and application thereof. Background Art
[0002] Lithium carbonate is the core component of lithium batteries. There are three main extraction routes: lithium extraction from spodumene, lithium extraction from mica and lithium extraction from salt lakes. Among them, lithium extraction from mica is the main method. However, due to the low grade of concentrate, mica lithium extraction technology requires 30-40 tons of lithium slag to smelt 1 ton of lithium carbonate, and the need for harmless and resourceful treatment of lithium slag is particularly prominent.
[0003] At present, the harmless treatment of lithium slag mainly involves adding reagents to remove beryllium and thallium after stirring and slurrying. However, when using the reagents in related technologies, both the pre-treatment and post-treatment are very complicated.
[0004] The main method is to add reagents to the lithium slag slurry to cause precipitation or flocculation to achieve the purpose of removing heavy metals in the lithium slag. The heavy metals are not solidified but only transferred. The by-product precipitate and flocculated slag obtained after dehydration and drying still have heavy metal leaching exceeding the standard and need to be disposed of as hazardous waste.
[0005] Therefore, it is necessary to provide a solution to achieve harmless products obtained after simple treatment of lithium slag and direct resource utilization. Summary of the invention
[0006] In view of this, the present application provides a solid waste synthesis activator and its preparation and application, which are used to solve the problem of how to improve the harmlessness and resource utilization of lithium slag.
[0007] In order to achieve the above technical objectives, this application adopts the following technical solutions:
[0008] In the first aspect, the present application provides a solid waste synthesis activator, comprising the following components in parts by mass: 25-35 parts of carbide slag, 10-20 parts of desulfurization gypsum, 5-10 parts of silica ash, 2-5 parts of glass powder, 1-3 parts of water reducer, 10-20 parts of heat-activated red mud, 5-15 parts of silicate, and 1-5 parts of regulator; the regulator includes nano alumina, and at least one of aluminum sulfate and sodium aluminate.
[0009] Preferably, the particle size of the silica fume is ≤18 μm, and the specific surface area of the silica fume is ≥15000 m 2 / kg; the mass ratio of the silica fume to the glass powder is 1:(0.2-1).
[0010] Preferably, the silicon-aluminum molar ratio of the solid waste synthesis activator is 1:(0.1-0.5), and the pH value of the solid waste synthesis activator is 11-13.
[0011] Preferably, the particle sizes of the carbide slag and the desulfurized gypsum are both ≤38 μm; the silicate is sodium silicate or potassium silicate; and the water content of the heat-activated red mud is ≤1wt%.
[0012] Preferably, the preparation step of the heat-activated red mud is: calcining the red mud at 700-750° C. for 30 min and then grinding it to a particle size of ≤38 μm to obtain the heat-activated red mud.
[0013] In the second aspect, the present application provides a method for preparing a solid waste synthetic activator, comprising the following steps: pre-treating carbide slag, desulfurization gypsum, silica ash, glass powder, and silicate respectively, mixing them with a regulator, and then adding a water reducer and heat-activated red mud to obtain the solid waste synthetic activator.
[0014] In a third aspect, the present application provides a harmless agent comprising a solid waste synthesis activator, which comprises a solid waste synthesis activator and granulated blast furnace slag powder in a mass ratio of 1:0.5-2.
[0015] Preferably, the specific surface area of the granulated blast furnace slag powder is 350-550m 2 / kg.
[0016] In a fourth aspect, the present application provides an application of a solid waste synthesis stimulator, comprising the following steps:
[0017] S1. Mixing the solid waste synthesis activator with the granulated blast furnace slag powder to obtain a harmless agent;
[0018] S2. Mix the harmless agent with the sieved lithium slag, add water, stir, age, and then landfill or recycle.
[0019] Preferably, the mass ratio of the solid waste synthesis activator to the granulated blast furnace slag powder is 1:(0.5-1), and the mass ratio of the harmless agent to the sieved lithium slag is 1:(10-20).
[0020] The beneficial effects of the present application are as follows: the present application uses a variety of solid waste materials as raw materials to treat lithium slag, thereby realizing the coordinated utilization of solid waste; the process of treating lithium slag waste using the solid waste synthetic stimulant of the present application is simple, does not produce polluting by-products, and has low cost; the solid waste synthetic stimulant of the present application introduces a regulator to improve the metal solidification effect, and the geopolymer obtained after treatment is harmless and can directly realize resource recycling. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0022] The present application provides a solid waste synthesis activator, comprising the following components in parts by mass: 25-35 parts of carbide slag, 10-20 parts of desulfurized gypsum, 5-10 parts of silica ash, 2-5 parts of glass powder, 1-3 parts of water reducer, 10-20 parts of heat-activated red mud, 5-15 parts of silicate, and 1-5 parts of regulator; the regulator comprises nano alumina, and at least one of aluminum sulfate and sodium aluminate.
[0023] The introduction of nano-alumina, sodium metaaluminate or aluminum sulfate in the regulator of the present application can adjust the silicon-aluminum ratio in the activator, improve the crystal structure of the aluminosilicate, and build a stable three-dimensional skeleton network architecture. At the same time, the introduction of aluminum atoms can improve the polarity of oxygen atoms in the lattice, thereby improving its electronegativity. Under the synergistic effect of the two effects, the migration of heavy metal ions such as beryllium and thallium in the lattice can be effectively slowed down, so that they are solidified in the skeleton of the three-dimensional structure and are no longer easily leached, thereby improving the heavy metal leaching of lithium slag, and at the same time improving the performance of the lithium slag treatment product (geopolymer), which is conducive to subsequent resource utilization. On the other hand, the activator of the present application contains alkaline raw materials such as carbide slag, heat-activated red mud, and silicates. Under the action of alkali excitation, the rate of hydration reaction can be increased, and part of calcium and sodium are provided for the formation of hydrated calcium aluminosilicate CASH and / or hydrated sodium aluminosilicate NASH gel, thereby improving the overall mechanical properties and heavy metal solidification effect of the geopolymer.
[0024] In some embodiments, the particle size of the silica fume is ≤18 μm, and the specific surface area of the silica fume is ≥15000 m 2 / kg, silica fume is one of the Si sources in the solid waste synthesis activator. Because of its high activity, silica fume provides active Si atoms in the system to increase the production of CASH, NASH, and CSH gels produced by hydration reactions, which is beneficial to the development of strength and the solidification of heavy metal ions. In addition, due to the small particle size of silica fume, some unreacted silica fume can fill the pores and prevent water migration from leaching heavy metal ions. The specific surface area of silica fume is ≥15000m 2 / kg, it is beneficial to improve the activity of silica fume, and the obtained geopolymer has high strength, which is beneficial to subsequent resource utilization.
[0025] In some embodiments, the D90 particle size of the glass powder is 20-60 μm, preferably, the D90 particle size of the glass powder is 30-50 μm. If the particle size of the glass powder is too small, its dispersibility is enhanced, making it easier for water to enter the material. The fine waste glass powder particles can fill the microscopic gaps in the material, forming more penetration paths, thereby increasing the penetration rate and penetration depth of water. If the particle size of the glass powder is too large, the mutual bonding performance between the calcium carbide slag, thermally activated red mud and desulfurized gypsum powder particles is reduced, and it is easy to form tiny gaps and cracks, which increases the penetration path of water molecules and thus increases the water absorption rate. When the D90 particle size of the glass powder is 20-60 μm, the absorption rate will not be too high or too low, that is, it can take into account the mutual bonding performance of the glass powder and other materials, and can better and not excessively fill the microscopic gaps in the material.
[0026] In some embodiments, the mass ratio of silica fume to glass powder is 1: (0.2-1). The use of the glass powder of the present application can reduce the low water absorption rate of the geopolymer material, but the flexural strength is low. By compounding with silica fume, the interface bonding between the filler and the matrix can be improved, and the interface peeling and crack propagation can be reduced, thereby improving the flexural strength of the lithium slag treatment product (geopolymer).
[0027] In some embodiments, the silicon-aluminum molar ratio of the solid waste synthesis activator is 1: (0.1-0.5), and the pH value of the solid waste synthesis activator is 11-13. The silicon-aluminum ratio within the above range can improve the crystal structure of aluminosilicates and build a stable three-dimensional skeleton network architecture. At the same time, the introduction of aluminum atoms can enhance the polarity of oxygen atoms in the lattice, improve its crystal structure, and form CSH and CASH (or NASH); wherein the adjustment of the silicon-aluminum ratio is achieved by introducing nano-alumina, sodium aluminate and / or aluminum sulfate into the regulator to adjust the active silicon-aluminum ratio in the solid waste synthesis activator, and the pH of the activator is adjusted by introducing carbide slag and thermally activated red mud.
[0028] In some embodiments, the particle size of carbide slag, thermally activated red mud, and desulfurized gypsum is ≤38 μm; and / or the water content of thermally activated red mud is ≤1%. Carbide slag, thermally activated red mud, and desulfurized gypsum have large specific surface areas, high activity, good hydration effects, and solidification and detoxification effects of heavy metals at the particle size specified in this application. The role of thermally activated red mud in this application is to provide an alkaline environment and Na + Ions are beneficial to the formation of NASH gel, and the red mud of the present application has a low water content. When the water content of the red mud is too high, the water in the red mud will first react with the activator to hydrate, thereby causing the activator to stimulate the red mud to have a poor activity effect, and the strength of the prepared geopolymer material is low.
[0029] In some embodiments, the water reducer is any one of a lignin sulfonate water reducer, a naphthalene water reducer, an aliphatic water reducer or a polycarboxylate water reducer, preferably a polycarboxylate water reducer.
[0030] The present application provides a method for preparing a solid waste synthesis activator, comprising the following steps: pre-treating carbide slag, heat-activated red mud, desulfurized gypsum, silica fume, and glass powder respectively, mixing them with a regulator, and then adding a water reducer to obtain the solid waste synthesis activator.
[0031] Among them, the pretreatment process of carbide slag is to dry the carbide slag, grind it in a vertical mill for 280-380 minutes and then grind it in a ball mill for 10-40 minutes; the preparation process of heat-activated red mud is to calcine the red mud at 700-750℃ for 30 minutes and then put it into a ball mill for grinding for 10-40 minutes; the pretreatment process of silica ash and glass powder is screening.
[0032] The present application provides a harmless agent comprising a solid waste synthesis activator, which comprises a solid waste synthesis activator and granulated blast furnace slag powder in a mass ratio of 1:0.5-2, wherein the slag is beneficial to improving the gelling activity of the lithium slag after activation;
[0033] In some embodiments, the specific surface area of the granulated blast furnace slag powder is 350-550m 2 / kg, under this specific surface area, the slag has good activity, which is conducive to the hydration reaction. If the specific surface area is too low, it will affect the curing effect and the mechanical strength of the geopolymer.
[0034] The present application provides an application of a solid waste synthesis activator, comprising the following steps:
[0035] S1. Mixing the solid waste synthesis activator with the granulated blast furnace slag powder to obtain a harmless agent;
[0036] S2. Mix the harmless agent with the screened lithium slag, add water, stir, age, and then landfill or regenerate.
[0037] In some embodiments, the mass ratio of the solid waste synthesis stimulator to the granulated blast furnace slag powder is 1: (0.5-2); and / or, the mass ratio of the solid waste synthesis stimulator to the screened lithium slag is 1: (10-20). The present application controls the amount of solid waste synthesis stimulator used in the harmless treatment of lithium slag. When the proportion of the solid waste synthesis stimulator is too low, the stimulation effect on the activity of the lithium slag is poor, which can easily cause incomplete solidification of heavy metals, and the heavy metal leaching results cannot meet the limit values required in the "Hazardous Waste Identification Standard Leaching Toxicity Identification GB5085.3-2007"; if the proportion of the solid waste synthesis stimulator is too high, on the one hand, the harmlessness cost will increase, and on the other hand, it will also cause the harmless product (geopolymer) to condense too quickly, the early strength is too high, and the difficulty of later transportation will be increased.
[0038] The present solution is further described below through specific embodiments.
[0039] Example 1
[0040] A solid waste synthesis activator, comprising the following components by weight: 30 parts of carbide slag with a particle size of 30 μm, 20 parts of desulfurized gypsum with a particle size of 28 μm, and 10 parts of a solid waste with a particle size of 3 μm and a specific surface area of 15000 m 2 / kg of silica fume, 4 parts of glass powder with a D90 particle size of 20μm, 2 parts of water reducer, 10 parts of sodium silicate, 5 parts of regulator, and 10 parts of heat-activated red mud with a moisture content of 0.2wt%; each part of regulator includes 4 parts of sodium aluminate and 1 part of nano alumina; under this ratio, the silicon-aluminum molar ratio of the solid waste synthesis activator is 1:0.5.
[0041] The preparation method of the solid waste synthesis activator is as follows: after drying the carbide slag at 110°C for 4 hours, grinding it in a vertical mill for 330 minutes and then grinding it in a ball mill at 300rpm for 40 minutes; after drying the red mud at 700°C for 30 minutes, putting it into a ball mill and grinding it at 300rpm for 40 minutes to obtain heat-activated red mud; the treated carbide slag, heat-activated red mud, sieved silica ash, glass powder, desulfurized gypsum, fly ash, sodium silicate and regulator are evenly stirred, and a water reducer is added to obtain the solid waste synthesis activator.
[0042] Example 2
[0043] A solid waste synthesis activator, the other contents are the same as those in Example 1, except that the mass fraction of the regulator is 1 part, and the components of the regulator are 1 / 5 of the components of the regulator in Example 1; under this ratio, the silicon-aluminum molar ratio of the solid waste synthesis activator is 1:0.2.
[0044] Example 3
[0045] A solid waste synthesis activator, the other contents are the same as those in Example 1, except that the particle size of the silica fume is 45 μm square hole sieve residue ≤ 5.0% and the specific surface area is ≥ 18000 m 2 / kg.
[0046] Example 4
[0047] A solid waste synthesis activator, other contents are the same as those in Example 1, except that the activation temperature of the thermally activated red mud is 150°C.
[0048] Example 5
[0049] An application of a solid waste synthesis activator comprises the following steps:
[0050] S1. respectively, the solid waste synthesis activator of Example 1 and the solid waste synthesis activator of Example 1 with a specific surface area of 550m 2 / kg granulated blast furnace slag powder is mixed to obtain a harmless agent; wherein the mass ratio of the solid waste synthesis activator to the granulated blast furnace slag powder is 1:1;
[0051] S2. Mix the harmless agent with the sieved lithium slag, add water, stir and age at room temperature and pressure, wherein the mass ratio of the sieved lithium slag, the harmless agent and water is 10:1:2, to obtain a geopolymer, which is then landfilled or regenerated.
[0052] Example 6
[0053] An application of a solid waste synthesis stimulant, the other contents are the same as those of Example 5, except that the solid waste synthesis stimulant of Example 1 is replaced by the solid waste synthesis stimulant of Example 2.
[0054] Example 7
[0055] An application of a solid waste synthesis stimulant, the other contents are the same as those of Example 5, except that the solid waste synthesis stimulant of Example 1 is replaced by the solid waste synthesis stimulant of Example 3.
[0056] Example 8
[0057] An application of a solid waste synthesis stimulant, the other contents are the same as those of Example 5, except that the solid waste synthesis stimulant of Example 1 is replaced by the solid waste synthesis stimulant of Example 4.
[0058] Example 9
[0059] Application of a solid waste synthesis activator, the other contents are the same as those in Example 5, except that the specific surface area is 550m 2 / kg granulated blast furnace slag powder is replaced with a specific surface area of 350m 2 / kg granulated blast furnace slag powder.
[0060] Example 10
[0061] Application of a solid waste synthesis activator, the other contents are the same as those in Example 5, except that the specific surface area is 550m 2 / kg granulated blast furnace slag powder is replaced with a specific surface area of 200m 2 / kg granulated blast furnace slag powder.
[0062] Comparative Example 1
[0063] A solid waste synthesis activator, the other contents are the same as those of Example 1, except that the regulator does not include sodium aluminate, and the other components are scaled in proportion.
[0064] Comparative Example 2
[0065] A solid waste synthesis activator, the other contents are the same as those in Example 1, except that the sodium aluminate in the regulator is replaced by aluminum sulfate.
[0066] Comparative Example 3
[0067] A solid waste synthesis activator, the other contents are the same as those of Example 1, except that the regulator does not include nano-alumina, and the other components are scaled in proportion.
[0068] Comparative Example 4
[0069] A solid waste synthesis activator, other contents are the same as those in Example 1, except that thermally activated red mud is not included.
[0070] Comparative Examples 5-7
[0071] A solid waste synthesis activator, the other contents are the same as those in Example 1, except that the amounts of the regulator are 0.5 parts, 10 parts, and 20 parts, respectively; and the components in the regulator are scaled in proportion to those in Example 1.
[0072] Comparative Examples 8-14
[0073] An application of a solid waste synthesis activator comprises the following steps:
[0074] S1. respectively, the solid waste synthesis activator of comparative examples 1-7 corresponding to the specific surface area of 550m 2 / kg granulated blast furnace slag powder is mixed to obtain a harmless agent; wherein the mass ratio of the solid waste synthesis activator to the granulated blast furnace slag powder is 1:1;
[0075] S2. Mix the harmless agent with the sieved lithium slag, add water, stir and age at room temperature and pressure, wherein the mass ratio of the sieved lithium slag, the harmless agent and water is 10:1:2, to obtain a geopolymer, which is then landfilled or regenerated.
[0076] Test and Evaluation
[0077] The same batch of sieved lithium slag raw materials was used in Examples 5-11 and Comparative Examples 8-14. The samples of sieved lithium slag raw materials, harmless products aged for 1 day, and harmless products (geopolymers) aged for 3 days in Examples 5-11 and Comparative Examples 8-14 were subjected to heavy metal detection of beryllium and thallium. The method was based on the "Hazardous Waste Identification Standard Leaching Toxicity Identification GB 5085.3-2007" and "Solid Waste Leaching Toxicity Leaching Method Sulfuric Acid and Nitric Acid Method HJ / T 299-2007". After testing, the content of beryllium Be in the sieved lithium slag raw material was 538.1 μg / L, and the content of thallium Tl was 87.3 μg / L; the experimental results of the harmless products aged for 1 day and the harmless products (geopolymers) aged for 3 days are shown in Table 1.
[0078] Table 1 Test results
[0079]
[0080]
[0081] Appendix: The 0.7 and 1.3 mentioned in the table are the lower limits of detection concentration of beryllium and thallium by the testing agency’s instruments. Values below this leaching concentration are marked as 0.7L and 1.3L after the lower limit.
[0082] As can be seen from Table 1, the addition of the aluminum-based regulator of the present application can significantly improve the performance of the curing agent in curing heavy metals and enhance the mechanical strength. After aging for 1 day, beryllium and thallium can reach below the limit of hazardous waste identification standards; the reduction in activation temperature of heat-activated red mud used in the present application has a greater impact on the overall effect of the curing agent; the use of granulated blast furnace slag powder with a larger specific surface area in the present application has a significant effect on improving the overall effect of the curing agent.
[0083] The present application uses a variety of solid waste materials as raw materials to treat lithium slag, thereby realizing the coordinated utilization of solid waste; the process of treating lithium slag waste using the solid waste synthetic activator of the present application is simple, does not produce polluting by-products, and has low cost; the solid waste synthetic activator of the present application introduces a regulator to improve the metal solidification effect, and the geopolymer obtained after treatment is harmless and can directly realize resource recycling.
[0084] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A solid waste synthesis activator, characterized in that: The composition comprises the following components in parts by weight: 25-35 parts of carbide slag, 10-20 parts of desulfurized gypsum, 5-10 parts of silica fume, 2-5 parts of glass powder, 1-3 parts of water reducing agent, 10-20 parts of heat-activated red mud, 5-15 parts of silicate, and 1-5 parts of regulator; The regulator includes nano alumina and at least one of aluminum sulfate and sodium aluminate.
2. The solid waste synthesis activator according to claim 1, characterized in that: The particle size of the silica fume is ≤18 μm, and the specific surface area of the silica fume is ≥15000 m 2 / kg; the mass ratio of the silica fume to the glass powder is 1:(0.2-1).
3. The solid waste synthesis activator according to claim 1, characterized in that: The silicon-aluminum molar ratio of the solid waste synthesis activator is 1:(0.1-0.5), and the pH value of the solid waste synthesis activator is 11-13.
4. The solid waste synthesis activator according to claim 1, characterized in that: The particle sizes of the carbide slag and the desulfurized gypsum are both ≤38 μm; the silicate is sodium silicate or potassium silicate; and the water content of the heat-activated red mud is ≤1wt%.
5. The solid waste synthesis activator according to claim 1, characterized in that: The preparation step of the thermally activated red mud is: calcining the red mud at 700-750° C. for 30 minutes and then grinding the red mud to a particle size of ≤38 μm to obtain the thermally activated red mud.
6. A method for preparing a solid waste synthesis activator according to any one of claims 1 to 5, characterized in that: The following steps are involved: The solid waste synthesis activator is obtained by pre-treating carbide slag, desulfurized gypsum, silica fume, glass powder and silicate respectively, mixing them with a regulator, and then adding a water reducing agent and heat-activated red mud.
7. A harmless agent comprising the solid waste synthesis stimulator according to any one of claims 1 to 5, characterized in that: The method comprises a solid waste synthesis activator and granulated blast furnace slag powder in a mass ratio of 1:0.5-2.
8. The detoxifying agent according to claim 7, characterized in that: The specific surface area of the granulated blast furnace slag powder is 350-550m 2 / kg.
9. An application of the solid waste synthesis activator according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Mixing the solid waste synthesis activator with the granulated blast furnace slag powder to obtain a harmless agent; S2. Mix the harmless agent with the sieved lithium slag, add water, stir, age, and then landfill or recycle.
10. The use according to claim 9, characterized in that: The mass ratio of the solid waste synthesis activator to the granulated blast furnace slag powder is 1:(0.5-1), and the mass ratio of the harmless agent to the sieved lithium slag is 1:(10-20).